The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/adhm.201601101
|View full text |Cite
|
Sign up to set email alerts
|

Human Skin 3D Bioprinting Using Scaffold‐Free Approach

Abstract: Organ in vitro synthesis is one of the last bottlenecks between tissue engineering and transplantation of synthetic organs. Bioprinting has proven its capacity to produce 3D objects composed of living cells but highly organized tissues such as full thickness skin (dermis + epidermis) are rarely attained. The focus of the present study is to demonstrate the capability of a newly developed ink formulation and the use of an open source printer, for the production of a really complete skin model. Proofs are given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
259
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(259 citation statements)
references
References 17 publications
0
259
0
Order By: Relevance
“…In another study by Pourchet and co-workers in Fig. 4b, the skin tissue was 3D bioprinted and further underwent consolidation and maturation, in which NIH 3T3 was embedded within gelatin, alginate and fibrinogen hydrogels [76]. It was found that the bioprinted skin and normal human skin showed similar optical microscopy images after 26 days of culture.…”
Section: Bioprinting Of Skinmentioning
confidence: 66%
“…In another study by Pourchet and co-workers in Fig. 4b, the skin tissue was 3D bioprinted and further underwent consolidation and maturation, in which NIH 3T3 was embedded within gelatin, alginate and fibrinogen hydrogels [76]. It was found that the bioprinted skin and normal human skin showed similar optical microscopy images after 26 days of culture.…”
Section: Bioprinting Of Skinmentioning
confidence: 66%
“…Recently, skin 3D bioprinting has achieved a significant progress [136] . For example, in 2016 Pourchet et al printed a full-thickness skin substitute containing dermis and epidermis layers [137] . A mixture of gelatin and fibrinogen was used as the "bioink".…”
Section: Skin 3d Bioprintingmentioning
confidence: 99%
“…In this regard, seminal studies have begun to optimize commonly used bioinks and explore new materials with more specialized, organ-specific properties. [197, 198] Still, more efforts are needed to fabricate novel bioinks that meet both cytocompatibility and mechanical strength requirements for 3D bioprinting.…”
Section: Perspectives/outlookmentioning
confidence: 99%